Training And Mentoring Google Apps For Education (GAFE) To Support Teacher Performance In Online Learning - Rose Fitria Lutfiana; Mayang Dintarini (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
The covid-19 pandemic has forced the education system in Indonesia to use the online method. This is explained in his research, which states that teachers have used various platforms such as Google Classroom, Edmodo, Zoom, or Schoology. The use of various learning platforms is considered a bit difficult, where teachers need to install various applications on their devices. Installing these various applications will certainly make the device work harder, so it’s possible for errors or hangs to occur when running the applications. The purpose of this mentoring activity is to provide training and mentoring on Google Apps for Education to teachers at SMA Panjura Malang. The method of implementing this community service activity begins with FGD, GAFE training, GAFE assistance and monitoring and evaluation of GAFE activities. The result of this service activity are: (1) service activities attended by 34 teachers, (2) pre test result are 41,1% and post test result are 91,1% so that there is an increase 50%, (3) 94% of teachers implement GAFE in learning.